Determining the sex of Little Penguins (Eudyptula minor) in northern Bass Strait using morphometric measurements - John Arnould; P Dann; Meghan Cullen (2004)
In avian species with no obvious differences in plumage or body size between the sexes, such as penguins, discriminant function analysis (DFA) of morphometric measurements that display sexual dimorphism can provide a simple and rapid means of determining sex in the field. Like most other penguin species, the Little Penguin ( Eudyptula minor ) displays sexual dimorphism in bill shape and size. In the present study, discriminant functions (DFs) were developed for sexing adult Little Penguins at two colonies in northern Bass Strait, Victoria, Australia, and their accuracies were compared with those obtained previously in other parts of the species' range. Backwards stepwise DFA indicated that birds at Phillip Island can be sexed with an accuracy of 91% using a single measurement of bill depth (>13.33 mm classed as males). Similar analyses at Gibson Steps produced a DF incorporating bill length, bill depth and head length [although the model with the greatest accuracy when applied to birds from Phillip Island (91%) also contained only bill depth]. Published DFs derived in New Zealand had accuracies of 50–85% when applied to birds from Phillip Island and Gibson Steps, supporting earlier suggestions that DFs are not applicable across subspecies of the Little Penguin. In contrast, there was little difference between the accuracy of the DFs in the present study and that previously derived for the same subspecies in Tasmania when applied to birds from Phillip Island (89%) and Gibson Steps (92%). However, as the degree of variation in bill size within a subspecies is unknown it may still be prudent to derive colony-specific DFs.